DEVELOP A NOVEL MARITIME CONTAINER TRANSPORT SYSTEM (Perner's Contacts, 2011)
This paper deals with new system of reloading of container in container terminals. Mid-stream operation is the operation of loading and unloading cargo containers at the container ship while at sea, with barges or dumb steel lighters performing the transfer, distribution or landing of containers to piers nearby. The goal of KAIST Mobile Harbor Project is to design and develop a novel maritime container transport system that can go out to a ship, anchoring in the deep water, to load/unload containers on sea and take them to their destination ports regardless of their water depth.
Keywords: container; reload; mobile harbor; ship